Granular Instrumental Variables - Gabaix, Xavier; Koijen, Ralph S. J. (Journal of Political Economy, 2024)
We develop a new method to construct instruments in a broad class of economic environments. In the economies we study, a few large firms, industries, or countries account for an important share of economic activity. Idiosyncratic shocks to these large players significantly affect aggregate outcomes and are valid instruments. We provide a methodology to extract these idiosyncratic shocks to create granular instrumental variables (GIVs), which are size-weighted sums of idiosyncratic shocks. We show how GIVs enable us to estimate causal parameters, such as elasticities and multipliers, and are applicable in a broad range of empirically relevant settings.
Keywords: Economic Activity; Economic Environments; Granular Instrumental Variables; Idiosyncratic Shocks